NMDAR activation attenuates the protective effect of BM-MSCs on bleomycin-induced ALI via the COX-2/PGE2 pathway - Xiao-Hong Li; Pu Huang; Hai-Peng Cheng; Yan Zhou; Dan-Dan Feng; Shao-Jie Yue; Yang Han; Zi-Qiang Luo (Heliyon, 2024)
N-methyl-d-aspartate (NMDA) receptor (NMDAR) activation mediates glutamate (Glu) toxicity and involves bleomycin (BLM)-induced acute lung injury (ALI). We have reported that bone marrow-derived mesenchymal stem cells (BM-MSCs) are NMDAR-regulated target cells, and NMDAR activation inhibits the protective effect of BM-MSCs on BLM-induced pulmonary fibrosis, but its effect on ALI remains unknown. Here, we found that Glu release was significantly elevated in plasma of mice at d 7 after intratracheally injected with BLM. BM-MSCs were pretreated with NMDA (the selective agonist of NMDAR) and transplanted into the recipient mice after the BLM challenge. BM-MSCs administration significantly alleviated the pathological changes, inflammatory response, myeloperoxidase activity, and malondialdehyde content in the damaged lungs, but NMDA-pretreated BM-MSCs did not ameliorate BLM-induced lung injury in vivo. Moreover, NMDA down-regulated prostaglandin E2 (PGE2) secretion and cyclooxygenase (COX)-2 expression instead of COX-1 expression in BM-MSCs in vitro. We also found that NMDAR1 expression was increased and COX-2 expression was decreased, but COX-1 expression was not changed in primary BM-MSCs of BLM-induced ALI mice. Further, the cultured supernatants of lipopolysaccharide (LPS)-pretreated RAW264.7 macrophages were collected to detect inflammatory factors after co-culture with NMDA-pretreated BM-MSCs. The co-culture experiments showed that NMDA precondition inhibited the anti-inflammatory effect of BM-MSCs on LPS-induced macrophage inflammation, and PGE2 could partially alleviate this inhibition. Our findings suggest that NMDAR activation attenuated the protective effect of BM-MSCs on BLM-induced ALI in vivo. NMDAR activation inhibited COX-2 expression and PGE2 secretion in BM-MSCs and weakened the anti-inflammatory effect of BM-MSCs on LPS-induced macrophage inflammation in vitro. In conclusion, NMDAR activation attenuates the protective effect of BM-MSCs on BLM-induced ALI via the COX-2/PGE2 pathway. Keywords: Acute Lung Injury, BM-MSCs, NMDA receptor, COX-1/2, PGE2.